Kajian Teoritis Persamaan Medan Gravitasi Einstein dengan Transformasi Metrik Schwarzschild dalam Sistem Dua Koordinat - sabam parsiholan simbolon (Saintia Fisika, 2013)
Teoritical studies have been made regarding the transformation of the Schwarzschild metric in two coordinates, the Schwarzschild metric transformation study in two coordinates: coordinates Cartesian and accelerated time-space uniform in no time flat spaces as well as local effects of a gravitational field in curved space. Gravitational field in curved space is chosen the Schwarzschild field is usually expressed in spatial space balls. Through these transformations, their metrics contain two people: (1) the rates associated with elements within the framework of the accelerated line uniform, and (2) the tribe associated with the curvature and geodesic deviation with regard to the effect of the curvature of space time. So that the results obtained from the existence of similarities between inertial mass and gravitational mass are relation with the theory of general relativity can explain local effect in the gravitational field. Key words: Transformation, coordinates, Schwarzschild’s metric